MAINSTREAM OF ELABORATION OF GEOPHYSICAL ACQUISITION FOR ESTIMATION OF SEISMIC HAZARD OF THE TERRITORY OF UKRAINE - Starostenko, V.; Kenszera, O.; Safronov, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The basic directions of geological and geophysical researches in the sphere of seismic hazard estimating for the territory of Ukraine, taking into account the requirements of State Building Codes B. 1.1-12:2006, are represented at the paper.